Artificial SEI film with lithium ion guiding function, and preparation method and application thereof

CN122889752APending Publication Date: 2026-10-09YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611057382.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,锂金属在沉积过程中易形成不规则的锂枝晶,枝晶会不断生长并穿透隔膜,导致电池内部短路、热失控等安全隐患;同时,锂枝晶的生长会破坏电极表面的固体电解质界面膜(SEI),导致SEI膜反复破裂与重建,消耗电解液和锂金属,显著降低电池的循环稳定性

Benefits of technology

(1)本发明提供的具有锂离子导向功能的人造SEI膜利用亲锂性纳米颗粒的“磁铁效应”引导锂离子均匀沉积,有效抑制锂枝晶生长,解决锂枝晶穿透的问题,很好地提升了电池的安全性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a kind of artificial SEI film with lithium ion guiding function and its preparation method and application, the artificial SEI film includes matrix material and nanoparticle dispersed in matrix material;The matrix material includes inorganic matrix and / or organic polymer matrix;The nanoparticle includes any one or combination of at least two of SnO2, ZnO, SiO2, Al2O3 or MgO;The structure of the artificial SEI film includes any one of single-layer structure, multilayer gradient structure or three-dimensional continuous structure.The artificial SEI film of the application utilizes the "magnet effect" of lithiumophilic nanoparticles to guide the uniform deposition of lithium ions, effectively inhibits the growth of lithium dendrites, can reduce the interface impedance of metal lithium battery, and improves the rate performance and cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and in particular to an artificial SEI film with lithium-ion guiding function, its preparation method and application. Background Technology

[0002] Lithium metal possesses an extremely high theoretical specific capacity (3860 mAh / g) and the lowest redox potential (-3.04 V vs standard hydrogen electrode), making it an ideal anode material for next-generation high-energy-density batteries. However, during the deposition process, lithium metal is prone to forming irregular lithium dendrites. These dendrites continuously grow and penetrate the separator, leading to safety hazards such as internal short circuits and thermal runaway. Simultaneously, the growth of lithium dendrites damages the solid electrolyte interphase (SEI) film on the electrode surface, causing repeated rupture and reconstruction of the SEI film, consuming electrolyte and lithium metal, and significantly reducing the cycle stability of the battery.

[0003] Traditional SEI films are formed by the spontaneous decomposition of electrolyte on the electrode surface, resulting in complex composition and non-uniform structure. Lithium ions exhibit low transport efficiency and uneven distribution within the SEI film, failing to effectively guide uniform lithium ion deposition and making it difficult to fundamentally suppress lithium dendrite growth. Existing improvement strategies include electrolyte additive modification, electrode surface modification, and solid electrolyte replacement, but these still suffer from limited effectiveness, complex preparation, and high cost. For example, while electrolyte additives can optimize SEI film composition, they are easily consumed during long-term cycling, resulting in insufficient stability; solid electrolytes have high interfacial impedance, and their ion conduction efficiency needs improvement.

[0004] Therefore, it is of great significance to develop an artificial SEI film with lithium-ion guiding function and its preparation method. Summary of the Invention

[0005] In view of the problems existing in the prior art, the present invention provides an artificial SEI film with lithium-ion guiding function, its preparation method and application. By utilizing the lithium-ion adsorption and guiding effect of nanoparticles, lithium ions are uniformly deposited in the matrix material, eliminating dendrite penetration and significantly improving battery safety. The artificial SEI film has a dense structure and uniform composition, high lithium-ion transport efficiency, and reduces battery interface impedance, making it suitable for widespread application in lithium metal batteries.

[0006] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides an artificial SEI film with lithium-ion guiding function, the artificial SEI film comprising a matrix material and nanoparticles dispersed in the matrix material; The matrix material includes an inorganic matrix and / or an organic polymer matrix; the nanoparticles include any one or a combination of at least two of SnO2, ZnO, SiO2, Al2O3 or MgO; the structure of the artificial SEI film includes any one of a single-layer structure, a multi-layer gradient structure or a three-dimensional continuous structure.

[0007] The nanoparticles in the artificial SEI film with lithium-ion guiding function described in this invention are lithium-philic metal compounds that react with lithium metal or lithium ions (e.g., SnO2 + 4Li). + +4e - →Sn+2Li2O), forming a metallic Sn / Li alloy or Li2O interface, exhibiting extremely high lithiophilicity and lithium-ion conductivity, enabling lithium-ion adsorption and directional guidance. Nanoparticles are uniformly dispersed in the artificial SEI film, forming a gradient distribution or vertical alignment, thereby creating lithium-ion transport channels extending outward from the negative electrode.

[0008] The matrix material in the artificial SEI film with lithium-ion guiding function described in this invention is used to bond and fix nanoparticles, and to provide basic ion conduction and electronic insulation. The inorganic matrix possesses high ionic conductivity and structural stability, which can improve the film density; the organic polymer matrix has good flexibility and adhesion, adapting to changes in lithium metal volume. The organic-inorganic composite matrix combines the high ionic conductivity and density of the inorganic matrix with the flexibility and adhesion of the organic matrix, balancing the mechanical strength and toughness of the film, making it the preferred matrix type for this invention.

[0009] The nanoparticles of the present invention include any one or a combination of at least two of SnO2, ZnO, SiO2, Al2O3 or MgO, wherein typical but non-limiting combinations include combinations of SnO2 and ZnO, combinations of SiO2 and Al2O3 or combinations of MgO and SnO2.

[0010] The structure of the artificial SEI film with lithium-ion guiding function described in this invention includes any one of a single-layer structure, a multi-layer gradient structure, or a three-dimensional continuous structure, wherein the multi-layer gradient structure and the three-dimensional continuous structure are preferred structures, which can achieve efficient directional guidance of lithium ions.

[0011] Preferably, the inorganic matrix includes any one or a combination of at least two of LiF, Li3N, Li2O or Li2CO3, wherein typical but nonlinear combinations include the combination of LiF and Li3N, the combination of Li2O and Li2CO3 or the combination of LiF and Li2O.

[0012] Preferably, the organic polymer matrix comprises any one or a combination of at least two of polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene, or polyacrylate, wherein typical but nonlinear combinations include a combination of polyethylene oxide and polyvinylidene fluoride-hexafluoropropylene, a combination of polyacrylate and polyethylene oxide, or a combination of polyvinylidene fluoride-hexafluoropropylene and polyacrylate.

[0013] Preferably, the nanoparticles include any one or a combination of at least two of SnO2, ZnO, SiO2, Al2O3, MgO and their dopants, wherein typical but nonlinear combinations include combinations of SnO2 and ZnO, combinations of SiO2 and Al2O3, or combinations of MgO and SnO2.

[0014] Preferably, the shape of the nanoparticles includes any one of spherical, rod-shaped, sheet-like, or porous structures.

[0015] Preferably, the average particle size of the nanoparticles is 1nm to 100nm, for example, it can be 1nm, 10nm, 25nm, 40nm, 70nm or 100nm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0016] Preferably, the nanoparticles of this invention have an average particle size of 1 nm to 100 nm, which can be uniformly dispersed in the SEI film.

[0017] Preferably, the nanoparticles are further nitrogen-doped and / or carbon-coated.

[0018] Preferably, the structure of the artificial SEI membrane includes a multi-layer gradient structure or a three-dimensional continuous structure.

[0019] Preferably, the organic polymer matrix further includes a lithium salt, which can improve ionic conductivity.

[0020] Preferably, the lithium salt comprises lithium bis(trifluoromethanesulfonyl)imide.

[0021] Preferably, the shape of the nanoparticles includes anisotropic nanorods or nanosheets, and the specific crystal facets have stronger lithiophilicity, which is more conducive to the directional transport of lithium ions.

[0022] Preferably, the average particle size of the nanoparticles is 20 nm, which provides the best ion guiding effect.

[0023] Preferably, the mass of nanoparticles in the single-layer artificial SEI film accounts for 700% to 900% of the mass of the matrix material, for example, 700%, 750%, 780%, 800%, 850% or 900%, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0024] Preferably, the thickness of the single-layer artificial SEI film is 3~8μm, for example, it can be 3μm, 4μm, 4.5μm, 5μm, 7μm or 8μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0025] The thickness of the single-layer artificial SEI film described in this invention is <3μm, which is insufficient in physical barrier ability and makes it difficult to completely suppress lithium dendrites; the thickness is >8μm: the film layer is too thick, which will increase the resistance to lithium ion transport, increase battery polarization, and reduce the rate and cycle performance of lithium battery.

[0026] Preferably, the multi-layered gradient structure of the artificial SEI film comprises, from the side closest to the lithium anode outwards, a guiding layer, a dense layer, and a buffer layer, with each layer having complementary and synergistic functions. Specifically, the guiding layer utilizes the "magnetic effect" of lithium-philic nanoparticles to adsorb lithium ions and guides them to uniformly deposit on the anode surface, preventing dendrite growth; the dense layer improves the ion conduction efficiency of the film and simultaneously forms a dense physical barrier layer, preventing lithium dendrite growth and penetration; the density of the film can be controlled through vacuum thermosetting; the buffer layer adapts to the volume expansion and contraction during lithium metal charging and discharging, preventing film cracking and detachment, while also reducing side reactions between the SEI film and the electrolyte, thus improving film stability.

[0027] Preferably, the guiding layer comprises a first matrix material and nanoparticles dispersed in the first matrix material.

[0028] Preferably, the first matrix material includes an inorganic matrix and / or an organic polymer matrix.

[0029] Preferably, the mass of the nanoparticles accounts for 60% to 80% of the mass of the first matrix material, for example, 60%, 64%, 68%, 72%, 76% or 80%, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0030] Preferably, the dense layer comprises a second matrix material and nanoparticles dispersed in the second matrix material.

[0031] Preferably, the second matrix material includes an inorganic matrix or an organic-inorganic composite matrix.

[0032] Preferably, the mass of the nanoparticles accounts for 10% to 20% of the mass of the second matrix material, for example, it can be 10%, 12%, 14%, 16%, 18% or 20%, etc., but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0033] Preferably, the buffer layer comprises an organic polymer matrix layer.

[0034] Preferably, the mass of nanoparticles in the three-dimensional continuous artificial SEI film accounts for 700% to 900% of the mass of the matrix material, for example, 700%, 750%, 780%, 800%, 850%, or 900%, but is not limited to the listed values; other unlisted values ​​within this range are also applicable. The nanoparticles form continuous or semi-continuous lithiophilic pathways extending outward from the negative electrode surface in the matrix material. The nanoparticles can achieve directional alignment through electric or magnetic field-assisted film formation. The lithiophilic pathways enable rapid and directional transport of lithium ions. Simultaneously, the matrix material fills the spaces between the lithiophilic pathways, ensuring the mechanical strength and electronic insulation of the film. This structure has the highest lithium-ion guiding efficiency among the three structures and is suitable for high-rate lithium metal batteries.

[0035] Preferably, the thickness of the artificial SEI film with the three-dimensional continuous structure is 3~8μm, for example, it can be 3μm, 4μm, 4.5μm, 5μm, 7μm or 8μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0036] Preferably, the thickness of the guiding layer is 1~3μm, for example, it can be 1.0μm, 1.4μm, 1.8μm, 2.2μm, 2.6μm or 3.0μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0037] Preferably, the thickness of the dense layer is 1~2μm, for example, it can be 1.0μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm or 2.0μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0038] Preferably, the thickness of the buffer layer is 1~3μm, for example, it can be 1.0μm, 1.4μm, 1.8μm, 2.2μm, 2.6μm or 3.0μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0039] Preferably, the total thickness of the artificial SEI film with the multilayer gradient structure is 3~8μm, for example, it can be 3.0μm, 4.0μm, 5.0μm, 6.0μm, 7.0μm or 8.0μm, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0040] Preferably, the total thickness of the artificial SEI membrane with the multi-layer gradient structure is 5 μm, which balances ion conduction and mechanical properties.

[0041] In a second aspect, the present invention also provides a method for preparing an artificial SEI film with lithium-ion guiding function as described in the first aspect, the method comprising: When preparing a single-layer artificial SEI film, a slurry of the matrix material is first prepared and nanoparticles are added to obtain a slurry to be treated; then the slurry to be treated is coated on a lithium foil, and then subjected to pre-drying treatment and vacuum thermosetting treatment in sequence to complete the preparation of the single-layer artificial SEI film. When preparing a multi-layer gradient structure artificial SEI film, the slurries to be treated are first prepared separately for the guiding layer, the dense layer, and the buffer layer; then the slurry to be treated for the guiding layer is coated on a lithium foil, and after drying, the slurry to be treated for the dense layer is coated on it, and after drying, the slurry to be treated for the buffer layer is coated on it; finally, the multi-layer structure artificial SEI film is prepared by sequentially undergoing pre-drying treatment and vacuum thermosetting treatment. When preparing a three-dimensional continuous artificial SEI film, a slurry of the matrix material is first prepared and nanoparticles are added to obtain a slurry to be treated; then the slurry to be treated is coated on a lithium foil and placed in a DC electric field or magnetic field for auxiliary treatment; finally, the three-dimensional continuous artificial SEI film is prepared by pre-drying treatment and vacuum thermosetting treatment.

[0042] The method for preparing the artificial SEI film with lithium-ion guiding function described in this invention is simple to operate. A specific amount of nanoparticles is added to a slurry of a substrate material to obtain a slurry to be treated. Then, according to the desired structure of the artificial SEI film, the slurry is coated onto a lithium foil. Finally, the film undergoes pre-drying and vacuum thermosetting treatments to complete the preparation of artificial SEI films with different structures. The artificial SEI film of this invention can achieve highly efficient directional guidance of lithium ions and inhibit lithium dendrite growth at its source, preventing dendrite penetration and significantly improving battery safety.

[0043] Preferably, the temperature of the pre-drying treatment is 20~30℃, for example, it can be 20℃, 22℃, 24℃, 26℃, 28℃ or 30℃, etc., but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0044] Preferably, the pre-drying time is 20-30 minutes, for example, 20 minutes, 22 minutes, 24 minutes, 26 minutes, 28 minutes or 30 minutes, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0045] Preferably, the heating rate of the vacuum thermosetting process is 1~1.5℃ / min, for example, it can be 1.0℃ / min, 1.1℃ / min, 1.2℃ / min, 1.3℃ / min, 1.4℃ / min or 1.5℃ / min, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0046] Preferably, the temperature of the vacuum thermosetting treatment is 60~70℃, for example, it can be 60℃, 62℃, 64℃, 66℃, 68℃ or 70℃, etc., but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0047] Preferably, the vacuum thermosetting treatment time is 12~14h, for example, it can be 12h, 12.5h, 12.8h, 13h, 13.5h or 14h, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0048] Preferably, the vacuum degree of the vacuum thermosetting process is <10Pa, for example, it can be 9.9Pa, 9.5Pa, 9Pa, 8Pa, 7Pa or 5Pa, etc., but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0049] Preferably, the electric field strength of the auxiliary treatment is 5~10V / cm, for example, it can be 5V / cm, 6V / cm, 7V / cm, 8V / cm, 9V / cm or 10V / cm, etc., but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0050] Preferably, the magnetic field strength of the auxiliary treatment is 0.5~1T, for example, it can be 0.50T, 0.60T, 0.70T, 0.80T, 0.90T or 1.00T, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0051] Preferably, the auxiliary processing time is 30 to 40 minutes, for example, it can be 30 minutes, 32 minutes, 34 minutes, 36 minutes, 38 minutes or 40 minutes, but it is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0052] Thirdly, the present invention also provides an application of an artificial SEI film with lithium-ion guiding function as described in the first aspect, wherein the artificial SEI film is used in a lithium metal battery.

[0053] The artificial SEI film described in this invention has a dense and uniform structure, resulting in high lithium-ion transport efficiency and effectively reducing battery interface impedance. When used in lithium metal batteries, it can significantly improve the battery's rate performance and cycle stability. Furthermore, the nanoparticles disperse the ion flow, effectively reducing the local current density on the negative electrode surface of the lithium metal battery.

[0054] Compared with the prior art, the present invention has at least the following beneficial effects: (1) The artificial SEI film with lithium-ion guiding function provided by the present invention utilizes the "magnetic effect" of lithium-loving nanoparticles to guide the uniform deposition of lithium ions, effectively suppressing the growth of lithium dendrites, solving the problem of lithium dendrite penetration, and greatly improving the safety of the battery. (2) The artificial SEI film with lithium-ion guiding function provided by the present invention has both mechanical strength and elasticity, and can adapt to the volume change during the battery cycle charging and discharging process; (3) The artificial SEI film with lithium-ion guiding function provided by the present invention has high lithium-ion transmission efficiency. When used in lithium metal batteries, it can effectively reduce the battery interface impedance, improve the rate performance and cycle stability of the battery, and is suitable for widespread application. Detailed Implementation

[0055] The present invention will now be described in further detail. However, the examples described below are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

[0056] Example 1 This embodiment provides a method for preparing a single-layer artificial SEI membrane, the method comprising: (1) Weigh 0.702 g of tin tetrachloride pentahydrate and dissolve it in 40 mL of anhydrous ethanol. Stir magnetically for 10 minutes and record as solution A. Weigh 1.8 g of urea and 0.8 g of hexadecyltrimethylammonium bromide and dissolve them in 40 mL of deionized water. Stir magnetically until completely dissolved and record as solution B. Under vigorous stirring, slowly add solution A to solution B to form a milky white suspension. Continue stirring for 30 minutes and then transfer the mixture to a 100 mL high-pressure reactor lined with polytetrafluoroethylene. Seal the reactor and place it in a forced-air drying oven. Perform a hydrothermal reaction at 180 °C for 18 hours to obtain 20 nm SnO2 particles with good crystallinity and uniform particle size. After the hydrothermal reaction is completed, allow it to cool naturally to 25 °C. Centrifuge the product (8000 rpm, 10 minutes) and wash it three times each with deionized water and anhydrous ethanol to remove impurities and unreacted ions. The obtained white precipitate was dried in a vacuum drying oven at 60°C for 12 hours to obtain SnO2 nanoparticles.

[0057] (2) Preparation of Tris-HCl buffer solution: Dissolve 0.606g Tris in 90mL of deionized water, adjust the pH to 8.5 with dilute hydrochloric acid, and then bring the volume to 100mL. Take 100mg of the above-mentioned dried SnO2 powder and ultrasonically disperse it in 80mL of the above-mentioned Tris-HCl buffer solution to form a uniform suspension. Weigh 80mg of dopamine hydrochloride and add it to the above suspension. Stir magnetically at 25℃ for 6 hours. Dopamine will spontaneously polymerize to form a uniform polydopamine coating on the surface of SnO2 particles, completing the polydopamine coating; the solution color will gradually turn brownish-brown. After the reaction is complete, collect the product by centrifugation (10000rpm, 10 minutes) and wash it three times with deionized water. Dry the product under vacuum at 60℃ for 6 hours to obtain SnO2@polydopamine intermediate. Place the SnO2@polydopamine intermediate in a quartz boat in a tube furnace. Under an argon protective atmosphere, the temperature was increased to 550°C at a rate of 5°C / min and held at this temperature for 2 hours. After the procedure, the mixture was naturally cooled to 25°C in an Ar atmosphere. The resulting black powder is SnO2@nitrogen-doped carbon-coated nanoparticles (SnO2@C).

[0058] (3) Measure 9.5 mL of N-methylpyrrolidone (NMP) into a 20 mL glass vial and place it on a magnetic stirrer. Weigh 0.100 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) powder and slowly add it to the NMP. Stir continuously in a 50°C water bath for 4 hours until completely dissolved to form a transparent and viscous PVDF-NMP solution. Weigh 0.900 g of SnO2@nitrogen-doped carbon-coated nanoparticles and slowly add them to the above PVDF solution in three batches under vigorous stirring. Stir for 30 minutes after each batch to ensure complete wetting and no large agglomerations. Transfer the above mixed slurry to the slurry tank of a planetary centrifuge. Stir at 2000 rpm revolution + 800 rpm rotation for 30 minutes to initially break up the agglomerates. Then, 5mm zirconia grinding balls were added, and the mixture was ball-milled at an intensity of 2000 rpm revolution + 1500 rpm rotation for 2 hours to ensure that the nanoparticles were uniformly and stably dispersed in the binder network without sedimentation. The slurry tank was then placed in a vacuum degassing mixer and stirred at low speed for 15 minutes under a vacuum of -0.1MPa to obtain a uniform black slurry with a viscosity of 4000cP and good flowability.

[0059] (4) Take a commercially available 20μm thick lithium foil and gently wipe the surface with a lint-free cloth soaked in anhydrous ethanol in a glove box filled with argon (H2O & O2 < 0.1ppm) to remove the oxide layer and impurities. Place the lithium foil flat on a heatable coating platform and fix the edges with vacuum adsorption to ensure absolute flatness. Use a precision doctor blade coater. Adjust the doctor blade gap to 80μm. Take an appropriate amount of the above slurry, place it at one end of the lithium foil, and push the doctor blade at a constant speed of 10mm / s to form a wet film on the surface of the lithium foil. The doctor blade gap and speed together determine the thickness of the wet film; an 80μm gap will eventually yield a dry film of about 5μm.

[0060] (5) After coating, immediately transfer the sample to the transition chamber of the glove box and let it stand at 25°C for 30 minutes to allow most of the NMP to evaporate slowly and prevent surface cracking. Transfer the sample to the vacuum drying oven connected to the glove box and slowly heat it to 60°C at 1°C / min, and keep it at 60°C for 12 hours. Maintain a high vacuum (<10Pa) throughout the process. Slow heating avoids rapid solvent evaporation, which may cause bubbles or cracks in the film. Long-term vacuum drying ensures that the solvent is completely removed, forming a dense film layer and obtaining a single-layer artificial SEI film.

[0061] Example 2 This embodiment provides a method for preparing a single-layer artificial SEI film. Except for obtaining 40nm SnO2 nanoparticles in step (1), the preparation method is the same as in Example 1.

[0062] Example 3 This embodiment provides a method for preparing a single-layer artificial SEI film. Except for step (1) which uses zinc nitrate hexahydrate as raw material to finally obtain 20nm ZnO nanoparticles, the preparation method is the same as in Example 1.

[0063] Example 4 This embodiment provides a method for preparing a single-layer artificial SEI film. Except for the thickness of the single-layer artificial SEI film obtained in step (5) being 1 μm, the preparation method is the same as in Example 1.

[0064] Example 5 This embodiment provides a method for preparing a single-layer artificial SEI film. Except for the thickness of the single-layer artificial SEI film obtained in step (5) being 10 μm, the preparation method is the same as in Example 1.

[0065] Example 6 This embodiment provides a method for preparing a multilayer gradient structure artificial SEI membrane. Steps (1), (2), and (5) of the preparation method are the same as in Example 1. Step (3) involves preparing the guiding layer slurry, the dense layer slurry, and the buffer layer slurry, as follows: a. Measure 9.5 mL of N-methylpyrrolidone (NMP) as solvent, add 0.100 g of PVDF-HFP, and stir in a 50°C water bath for 4 hours until completely dissolved; add 0.900 g of SnO2@C composite nanopowder in three batches, stirring for 30 minutes after each batch; transfer to a planetary centrifuge and stir at 2000 rpm + 800 rpm for 30 minutes; add 5 mm zirconia grinding balls and ball mill at 2000 rpm + 1500 rpm for 2 hours; degas under a vacuum of -0.1 MPa for 15 minutes to obtain the guiding layer slurry; b. Using LiF-Li3N (mass ratio 1:1) as the inorganic matrix. Measure 9.5 mL of NMP, add 0.200 g of PVDF and 0.800 g of LiF-Li3N mixture, and add a small amount of 0.100 g of SnO2@C nanoparticles; repeat the above dispersion, ball milling, and degassing steps to obtain a dense slurry. c. Using PVDF-HFP as the organic matrix. Measure 9.5 mL of NMP, add 0.300 g of PVDF-HFP, and add 0.05 g of LiTFSI lithium salt; repeat the above dispersion, ball milling, and degassing steps to obtain the buffer layer slurry.

[0066] Step (4) involves applying the guiding layer slurry, the dense layer slurry, and the buffer layer slurry in stages, as detailed below: Take a commercially available 20μm thick lithium foil and wipe the surface with a lint-free cloth soaked in anhydrous ethanol in an argon glove box (H2O & O2 < 0.1ppm) to remove the oxide layer and impurities. Place the lithium foil flat on a heatable coating platform and fix the edges by vacuum adsorption. Using a precision blade coater, first adjust the blade gap to 40μm and coat the guiding layer slurry on the lithium foil surface at a speed of 10mm / s to form a guiding layer wet film. After pre-drying at 25℃ for 15 minutes, adjust the blade gap to 30μm and coat the dense layer slurry. After pre-drying at 25℃ for another 15 minutes, adjust the blade gap to 40μm and coat the buffer layer slurry to form a multi-layer wet film.

[0067] In this embodiment, the thickness of the guiding layer in the multilayer gradient structure of the artificial SEI film is 2.5 μm, the thickness of the dense layer is 1.9 μm, and the thickness of the buffer layer is 2.5 μm.

[0068] Example 7 This embodiment provides a method for preparing a multilayer gradient structure artificial SEI film. The preparation method is the same as in Example 6, except that the heating rate of the vacuum drying oven in step (5) is replaced with 0.5℃ / min instead of 1℃ / min.

[0069] Example 8 This embodiment provides a method for preparing a multilayer gradient structure artificial SEI film. The preparation method is the same as in Example 6, except that the heating rate of the vacuum drying oven in step (5) is changed from 1℃ / min to 2℃ / min.

[0070] Example 9 This embodiment provides a method for preparing a multilayer gradient structure artificial SEI film. The preparation method is the same as in Example 6, except that the temperature of the vacuum drying oven in step (5) is replaced with 50°C instead of 60°C.

[0071] Example 10 This embodiment provides a method for preparing a multilayer gradient structure artificial SEI film. The preparation method is the same as in Example 6, except that the temperature of the vacuum drying oven in step (5) is replaced with 80°C instead of 60°C.

[0072] Example 11 This embodiment provides a method for preparing a three-dimensional continuous artificial SEI film. The steps (1) to (4) of the preparation method are the same as those in Example 1. In step (4), after forming a wet film on the surface of the lithium foil, the film is placed in a DC electric field with an electric field strength of 8V / cm for 35 minutes for auxiliary treatment. Then, step (5) is performed to obtain a three-dimensional continuous artificial SEI film.

[0073] The thickness of the artificial SEI membrane with a three-dimensional continuous structure prepared in this embodiment is 5 μm.

[0074] The artificial SEI films prepared in Examples 1-11 above were assembled with pure lithium foil anodes to form CR2032 coin-type lithium metal batteries. The positive electrode was LiFePO4, the electrolyte was a 1 mol / L LiPF6 EC / DMC / EMC (volume ratio 1:1:1) mixed electrolyte, and the separator was Celgard2400. Cyclic performance tests were conducted, and the coulombic efficiency and capacity retention data obtained are shown in Table 1.

[0075] Comparative Example 1 This comparative example provides a lithium metal battery that includes a lithium foil but does not additionally provide an artificial SEI film.

[0076] The lithium metal battery in Comparative Example 1 was also tested for cycle performance using the same method, and the results of the coulombic efficiency and capacity retention are shown in Table 1. As can be seen from Table 1: (1) The artificial SEI film provided by the present invention can significantly improve the coulombic efficiency and cycle stability of lithium metal batteries. As can be seen from the comparison of Examples 1 to 3 and Comparative Example 1, the artificial SEI film with a single layer structure of 20nm SnO2@C nanoparticles in Example 1 has the best effect. In Example 2, the ion guiding efficiency of 20nm SnO2@C nanoparticles is slightly reduced due to the increase in particle size. In Example 3, the lithium affinity of ZnO nanoparticles is slightly lower than that of SnO2@C. Therefore, the coulombic efficiency and capacity retention of lithium metal batteries are smaller than those in Example 1, but still far superior to the ordinary lithium foil anode without additional artificial SEI film in Comparative Example 1. (2) As can be seen from Examples 1 and 4-5, the thickness of the artificial SEI film with a single-layer structure in Example 4 is 1 μm, which is insufficient in physical blocking ability and cannot completely suppress lithium dendrites, resulting in a low coulombic efficiency of the lithium metal battery; the thickness of the artificial SEI film with a single-layer structure in Example 5 is 10 μm. The film layer is too thick, which will increase the resistance to lithium ion transport, increase battery polarization, and result in a low capacity retention rate of the lithium metal battery.

[0077] (3) As can be seen from Examples 6 and 7-10, the heating rate of the vacuum drying oven in Example 7 is relatively small, which leads to uncontrollable side reactions between the residual solvent (NMP) and trace amounts of moisture and the Li3N component. Impurities appear in the dense layer of the prepared multilayer gradient artificial SEI film. The heating rate of the vacuum drying oven in Example 8 is relatively large, which leads to the rapid evaporation of the solvent (NMP) in the slurry. Severe shrinkage stress is generated inside the film layer, and the dense layer structure of the prepared multilayer gradient artificial SEI film becomes loose and porous, and even cracks are generated. The temperature of the vacuum drying oven in Example 9 is relatively low, which leads to excessive NMP solvent residue in the dense layer of the prepared multilayer gradient artificial SEI film, which blocks the Li3N component. + The high temperature of the vacuum drying oven in Example 10 can lead to the decomposition of PVDF polymer or harmful side reactions with SnO2@C nanopowder. Cracks and pores appear in the dense layer of the prepared multilayer gradient structure artificial SEI film. These changes will result in lower coulombic efficiency and capacity retention of the lithium metal battery compared to Example 6.

[0078] (4) As can be seen from Examples 1, 6, and 11, the artificial SEI films with single-layer, multi-layer gradient, or three-dimensional continuous structures provided by the present invention can guide the uniform deposition of lithium ions, effectively suppress lithium dendrite growth, and thus reduce the interface impedance of lithium metal batteries, resulting in high coulombic efficiency and capacity retention. It should be noted that the above descriptions are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the scope of protection and disclosure of the present invention.

Claims

1. A synthetic SEI film with lithium-ion guiding function, characterized in that, The artificial SEI film comprises a matrix material and nanoparticles dispersed in the matrix material; The matrix material includes an inorganic matrix and / or an organic polymer matrix; the nanoparticles include any one or a combination of at least two of SnO2, ZnO, SiO2, Al2O3 or MgO; The structure of the artificial SEI membrane includes any one of a single-layer structure, a multi-layer gradient structure, or a three-dimensional continuous structure.

2. The artificial SEI membrane according to claim 1, characterized in that, The inorganic matrix includes any one or a combination of at least two of LiF, Li3N, Li2O or Li2CO3; Preferably, the organic polymer matrix comprises any one or a combination of at least two of polyethylene oxide, polyvinylidene fluoride-hexafluoropropylene, or polyacrylate; Preferably, the shape of the nanoparticles includes any one of spherical, rod-shaped, sheet-like, or porous structures; Preferably, the average particle size of the nanoparticles is 1 nm to 100 nm; Preferably, the nanoparticles are further nitrogen-doped and / or carbon-coated; Preferably, the structure of the artificial SEI membrane includes a multi-layer gradient structure or a three-dimensional continuous structure.

3. The artificial SEI membrane according to claim 2, characterized in that, The organic polymer matrix also includes lithium salt; Preferably, the lithium salt comprises lithium bis(trifluoromethanesulfonyl)imide; Preferably, the shape of the nanoparticles includes anisotropic nanorods or nanosheets; Preferably, the average particle size of the nanoparticles is 20 nm.

4. The artificial SEI membrane according to any one of claims 1 to 3, characterized in that, In the single-layer structured artificial SEI film, the mass of nanoparticles accounts for 700% to 900% of the mass of the matrix material; Preferably, the thickness of the single-layer artificial SEI film is 3~8μm; Preferably, the multilayer gradient structure of the artificial SEI film includes, from the side closest to the lithium anode outwards, a guiding layer, a dense layer, and a buffer layer. Preferably, the guiding layer comprises a first matrix material and nanoparticles dispersed in the first matrix material; Preferably, the first matrix material comprises an inorganic matrix and / or an organic polymer matrix; Preferably, the mass of the nanoparticles accounts for 700% to 900% of the mass of the first matrix material; Preferably, the dense layer comprises a second matrix material and nanoparticles dispersed in the second matrix material; Preferably, the second matrix material comprises an inorganic matrix or an organic-inorganic composite matrix; Preferably, the mass of the nanoparticles accounts for 10% to 20% of the mass of the second matrix material; Preferably, the buffer layer comprises an organic polymer matrix layer; Preferably, the mass of nanoparticles in the three-dimensional continuous structure artificial SEI film accounts for 700% to 900% of the mass of the matrix material; Preferably, the thickness of the artificial SEI film with the three-dimensional continuous structure is 3~8μm.

5. The artificial SEI membrane according to claim 4, characterized in that, The thickness of the guiding layer is 1~3μm; Preferably, the thickness of the dense layer is 1~2 μm; Preferably, the thickness of the buffer layer is 1~3μm; Preferably, the total thickness of the artificial SEI membrane with the multilayer gradient structure is 3~8μm.

6. The artificial SEI membrane according to claim 5, characterized in that, The total thickness of the artificial SEI membrane with the multi-layer gradient structure is 5 μm.

7. A method for preparing an artificial SEI film with lithium-ion guiding function as described in any one of claims 1 to 6, characterized in that, The preparation method includes: When preparing a single-layer artificial SEI film, a slurry of the matrix material is first prepared and nanoparticles are added to obtain a slurry to be treated; then the slurry to be treated is coated on a lithium foil, and then subjected to pre-drying treatment and vacuum thermosetting treatment in sequence to complete the preparation of the single-layer artificial SEI film. When preparing a multi-layer gradient structure artificial SEI film, the slurries to be treated are first prepared separately for the guiding layer, the dense layer, and the buffer layer; then the slurry to be treated for the guiding layer is coated on a lithium foil, and after drying, the slurry to be treated for the dense layer is coated on it, and after drying, the slurry to be treated for the buffer layer is coated on it; finally, the multi-layer structure artificial SEI film is prepared by sequentially undergoing pre-drying treatment and vacuum thermosetting treatment. When preparing a three-dimensional continuous artificial SEI film, a slurry of the matrix material is first prepared and nanoparticles are added to obtain a slurry to be treated; then the slurry to be treated is coated on a lithium foil and placed in a DC electric field or magnetic field for auxiliary treatment; finally, the three-dimensional continuous artificial SEI film is prepared by pre-drying treatment and vacuum thermosetting treatment.

8. The preparation method according to claim 7, characterized in that, The temperature for the pre-drying treatment is 20~30℃; Preferably, the pre-drying treatment time is 20-30 minutes; Preferably, the heating rate of the vacuum thermosetting treatment is 1~1.5℃ / min; Preferably, the temperature of the vacuum thermosetting treatment is 60~70℃; Preferably, the vacuum thermosetting treatment takes 12-14 hours; Preferably, the vacuum degree of the vacuum thermosetting process is <10 Pa.

9. The preparation method according to claim 7, characterized in that, The electric field strength of the auxiliary treatment is 5~10V / cm; Preferably, the magnetic field strength for the auxiliary treatment is 0.5~1T; Preferably, the auxiliary processing time is 30-40 minutes.

10. An application of an artificial SEI film with lithium-ion guiding function as described in any one of claims 1 to 6, characterized in that, The artificial SEI film is used in lithium metal batteries.